Akparabong and Yalla-Nkum Relations in the Middle Cross River Region, Nigeria - Enor, Frank N.; Etta, Kenneth Obem (International Journal of Law and Society, 2023)
People and cultures migrating from one location to another is thought to be a long-standing historical trend. This is essentially true during the formative stages of nation-states. Internal and external factors more frequently induced the movement of a diverse range of people in groups or trickled them to habitations deemed more favourable, secure, or conducive to farming, settlement, hunting, and so on. Wars, slave raids, hostile neighborhoods, or the search for resources like water, salt ponds, and so on, constituted the push and pull factors of early migrations of populations. This paper considers the migrations and settlement of Yalla-Nkum and Akparabong and their impact on intergroup relations in Ikom, middle Cross River Region, from 1815–2007. The raison d’être and the factors of contacts and relations in determining the politics of Ikom have all been considered. The empirical phenomenological approach used in this study. Checking data is based on information obtained from informed informants. Documented sources also complement the primary data obtained. Findings show that ownership and management of scarce resources attract envy, hostility, and even resource conflicts among pre-colonial groups, thereby setting the pattern of relationships during the colonial era.